Persepsi Masyarakat tentang Haramnya Investasi di Pasar Modal Syariah - Hidayah, Noor Laili; Aslicha, Ghina; Hana, Kharis Fadlullah (TAWAZUN: Journal of Sharia Economic Law, 2020)
Public knowledge must also be comprehensive with the times. People are already familiar with the word "investment".  However, everyone's perception of investing in the Islamic capital market is different.  The negative public perception about the illicit investment in the Islamic capital market should not exist.  Many people think about halal or illicit investment that caused a lot of debate.  Halal perception comes from people who have been well educated and deeply educated.  Unlawful perception arises from the lack of public education about all aspects that exist in the Islamic capital market.  The purpose of this study is to prove that negative perceptions that mention investment is an unlawful activity is wrong and changing that notion into investment is a halal activity.  The results of this study indicate that some people who have negative perceptions come from people who have not been educated about investing in the Islamic capital market.  So, public education about investment in the Islamic capital market on all aspects needs to be improved, not only at the academic level but other aspects so that debate in the community about halal or illicit investment in the Islamic capital market need not be there.